PECULIARITIES OF STRUCTURE FORMATION IN CHROME-MOLYBDENIC STEEL AT CONTINUOUS COOLING - V. A. Lutsenko; N. I. Anelkin; T. N. Panfilova; L. A. Drobyshovskij (Литьë и металлургия)
Influencing of speed of cooling on formation of structure in the steel 42Cr4Mo2 is studied. It is shown, that at the continuous cooling with speeds in the range of 0,03-0,4°C/s in this steel the formation of ferrite-pearlite structure is priority, inure of steel has striped, which is conditioned to dendrites by chemical heterogeneity.